Implementasi Bahasa Indonesia Sebagai Bahasa Pemersatu: Analisis Bahasa di Tanah Papua - Abdul Azis Khoiri; Nurul Dwi Mutia (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
Language is a communication tool for every human being in everyday life to establish interactions in the social environment. This research is a case study that discusses the analysis of language varieties in Papua. The type of research used in compiling this research is using descriptive qualitative with the inclusion of a literature review method. Furthermore based on the resulth of research that has been carried out, it was found that there are more than 300 regional languages in Papua, and the object of regional language revitalization in Papua in 2023 consists of 9 languages. Therefore to connect communication between the people, the use of Indonesian implemented among the Papuan people, however its implementation, has its own characteristic, because the Papuan people want fast andconcise language use.